2020
DOI: 10.1016/j.sajb.2020.05.018
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical profile, antioxidant and antibacterial activity of four Hypericum species from the UK

Abstract: Treatment of skin wounds is an important domain in biomedical research since many pathogenic bacteria can invade the damaged tissues causing serious infections. Effective treatments are required under such conditions to inhibit microbial growth. Plants are traditionally used for the treatment of skin infections due to their antimicrobial potential. The antibacterial activity of different solvent extracts of four Hypericum species (H. androsaemum, H. ericoides, H. x moserianum and H. olympicum) traditionally ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…In addition to well-established pharmacological properties (i.e., antidepressant, antioxidant, etc. ), some Hypericum species were cited as possessing antibacterial and/or antifungal activity, proven by in vitro methods [ 22 , 44 , 45 , 46 , 47 ]. In this regard, we aimed to conduct a comparative evaluation of the antimicrobial potential of the extracts obtained from H. perforatum , H. alpigenum and H. rochelii , highlighting the main differences between this species in terms of antibacterial and antifungal effectiveness.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to well-established pharmacological properties (i.e., antidepressant, antioxidant, etc. ), some Hypericum species were cited as possessing antibacterial and/or antifungal activity, proven by in vitro methods [ 22 , 44 , 45 , 46 , 47 ]. In this regard, we aimed to conduct a comparative evaluation of the antimicrobial potential of the extracts obtained from H. perforatum , H. alpigenum and H. rochelii , highlighting the main differences between this species in terms of antibacterial and antifungal effectiveness.…”
Section: Resultsmentioning
confidence: 99%
“…The results obtained in the TPC assay agree with the data reported earlier (16), who described high polyphenol content (100.37 mg GAE/g plant dry material) in H. juniperinum. Moreover, in studies with different Hypericum species, the ethyl acetate extract showed the highest content of phenolic compounds, while the hexane and chloroform fractions were relatively poor in this kind of compounds (20). Studies on other Hypericum species showed that less polar solvents than water tend to perform better scavenging activity on DPPH and ABTS assays.…”
Section: Phenolic Content and Antioxidant Activity Assaysmentioning
confidence: 96%
“…The antioxidant capacity of a huge spectrum of other Hypericum species, mainly from Europe, have been studied. H. androsaemum, H. ericoides, H. moserianum, H. olympicum and H. triquetrifolium have been evaluated for TPC, flavonoid content and radical scavenging activity (20). Taking into account that H. juniperinum and H. mexicanum belong to the same genus of H. perforatum, the extracts obtained are expected to contain metabolites with considerable antioxidant properties (21).…”
Section: Introductionmentioning
confidence: 99%
“…Prospecting for plants that are rich in phenolic compounds is supported by studies highlighting the strong correlation between phenolic content and antioxidant capacity [ 64 ]. Furthermore, compounds exhibiting an antioxidant capacity tend to present other activities, such as anti-diabetic [ 65 ], anti-inflammatory [ 66 ], antibacterial [ 67 , 68 , 69 ] and antiproliferative activities [ 70 ]. Determining the antioxidant capacity by means of the ORAC assay is one of the best methods currently used [ 71 , 72 ].…”
Section: Discussionmentioning
confidence: 99%